2014
DOI: 10.1103/physrevb.90.085144
|View full text |Cite
|
Sign up to set email alerts
|

CuSe-based layered compoundBi2YO4Cu2Se2as a quasi-two-d

Abstract: We have investigated the physical properties of a new layered oxyselenide Bi2YO4Cu2Se2, which crystallizes in an unusual intergrowth structure with Cu 2 Se 2 and Bi2YO4 layers. Electric transport measurement indicates that Bi2YO4Cu2Se2 behaves metallic. Thermal transport and Hall measurements show that the type of the carriers is hole-like and it may be a potential thermoelectric material at high temperatures. First principle calculations are in agreement with experimental results and show that Bi2YO4Cu2Se2 is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…However, even though crystallography-wise these two layered materials can be described as natural superlattices, they present parabolic density of states (DOS) as a classical three-dimensional (3D) system rather than step-like ones. [14][15][16] The two phases, BiOCuSe and Bi 2 YO 4 Cu 2 Se 2 , present sharply different temperature dependencies of electrical properties (see Figure 2). The resistivity (ρ) of BiOCuSe first decreases with decreasing temperature and then rises below ca.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…However, even though crystallography-wise these two layered materials can be described as natural superlattices, they present parabolic density of states (DOS) as a classical three-dimensional (3D) system rather than step-like ones. [14][15][16] The two phases, BiOCuSe and Bi 2 YO 4 Cu 2 Se 2 , present sharply different temperature dependencies of electrical properties (see Figure 2). The resistivity (ρ) of BiOCuSe first decreases with decreasing temperature and then rises below ca.…”
Section: Resultsmentioning
confidence: 98%
“…In BiOCuSe, the oxide and selenide blocks consist of edge-shared OBi 4 [14] already concluded that the valence band maximum (VBM) of Bi 2 YO 4 Cu 2 Se 2 is composed of hybridized Cu (d xy + d yz ) and Se (p x + p y ) states but negligible Se p z contribution to the interlayer conduction. However, even though crystallography-wise these two layered materials can be described as natural superlattices, they present parabolic density of states (DOS) as a classical three-dimensional (3D) system rather than step-like ones.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations